А) 5х + (-х + 4) = 2х - 4(-3х + 2)
б) 23 - 14 х = 2х - 1

bokkvika2908 bokkvika2908    1   19.10.2021 00:12    0

Ответы
Lenokin88 Lenokin88  19.10.2021 01:00

а) х=1.2

б) х=1.5

Сделай лучшим ответом, буду признателен)


А) 5х + (-х + 4) = 2х - 4(-3х + 2)б) 23 - 14 х = 2х - 1
ПОКАЗАТЬ ОТВЕТЫ
топ2006 топ2006  19.10.2021 01:00

Объяснение:

a) 5х + (-х + 4) = 2х - 4(-3х + 2)

5x-x+4=2x+12x-8

4x+4=14x-8

14x-4x=8+4

10x=12

X=12/10

X=1,2

б) 23 - 14 х = 2х - 1

14x+2x=23+1

16x=24

X=24/16

X=3/2

X=1,5

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра